Sistema de suporte à decisão para seleção de sistemas de tratamento de esgoto no âmbito de bacias hidrográficas - Almeida, Karinnie Nascimento de (2022)
Sewage treatment systems selection is a complex problem when analyzed in the context of hydrographic basins. It involves the joint analysis of environmental, technological, operational and social aspects associated with the treatment systems, in addition to raw or treated sewage final disposal receiving watercourses support capacity assessments. The present work aims to propose a methodology that could help the sewage treatment systems selection process through the combined application of a water quality mathematical model, metaheuristic optimization technique (Genetic Algorithm) and multicriteria analysis method (Theory of Multi-attribute utility). The research study area was the hydrographic basin of the Benevente River, an important watercourse located in the southern portion of the Espírito Santo state, Brazil. Minimum efficiencies for removing organic matter and nutrients were considered in the sewage treatment systems pre-selection. For the most populous districts, such as Jabaquara, Alfredo Chaves and Alto Pongal, the ordering process, supported by multicriterial analysis, led to the selection of mechanized technology - an activated sludge process variation. For all other locations, stabilization pond systems variations were selected. The selected sewage treatment technologies were more restrictive as more water quality parameters were considered for the selection of technologies.